The significance of pretreatment anemia in the era of R‐IPI and NCCN‐IPI prognostic risk assessment tools: a dual‐center study in diffuse large B‐cell lymphoma patients. (26th March 2015) - Troppan, Katharina T.; Melchardt, Thomas; Deutsch, Alexander; Schlick, Konstantin; Stojakovic, Tatjana; Bullock, Marc D.; Reitz, Daniel; Beham‐Schmid, Christine; Weiss, Lukas; Neureiter, Daniel; Wenzl, Kerstin; Greil, Richard; et al.
Abstract: Background: Anemia is frequently identified at the time of diagnosis in patients with diffuse large B‐cell lymphoma (DLBCL); however, studies addressing the prognostic significance of this important clinical parameter are lacking. Methods: In this dual‐center study of patients with DLBCL ( n = 556) treated with rituximab‐containing regimens, we evaluated the prognostic relevance of anemia at diagnosis in a training set ( n = 211) and validated our findings in a second independent patient cohort ( n = 345). Using Kaplan–Meier curves as well as univariate and multivariate Cox regression models, we analyzed the impact of anemia on 5‐year overall survival (OS) and 5‐year disease‐free survival (DFS) alongside established prognostic indicators including age, tumor stage, the revised International Prognostic Index (R‐IPI), and the recently published NCCN‐IPI. The influence of anemia on the predictive accuracy of IPI, R‐IPI, and NCCN‐IPI prognosis scores was subsequently determined using the Harrell's concordance index. Results: Anemia was an independent predictor of impaired OS and DFS at 5 years in both DLBCL patient cohorts ( P < 0.001, log–rank test). In multivariate analysis, hemoglobin level was also a strong and independent prognostic indicator in patients stratified according to R‐IPI or NCCN‐IPI score. In survival analysis, the estimated concordance index, using IPI, R‐IPI, and NCCN‐IPI stratification measures (0.69, 0.64, and 0.70, respectively), improved to 0.70, 0.68, and 0.73, respectively, when anemia was also considered. Conclusion: In this study, we have demonstrated that anemia at the time of diagnosis is an independent predictor of impaired clinical outcome in DLBCL. Furthermore, consideration of hemoglobin levels may improve the accuracy of recently established prognostic tools in lymphoma. Our data encourage further evaluation of the prognostic utility of this readily accessible biological parameter in prospective clinical trials.